IMPROVING LEARNERS’ READING SKILL THROUGH ADVERTISEMENT - Zulkifli - - (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2011)
People do different things with their language and they expect to achieve a large number of different aims and purposes by talking and writing, and by listening and reading (Halliday & Hasan, 1989:16). In a reading classroom, teachers need to provide the learners reading exercises related to implicit message of the text. Thus, they would require more critical reading and thinking than just comprehension for factual questions. In this case, the use of authentic materials-that is materials, which are not specifically designed for pedagogical purposes- would be advisable to  improve learner’s reading skills. The purpose of using authentic reading materials is to give learners the skill to cope with the think they might need to interpret in their real life reading. The authentic reading materials selected here are advertisement on billboards that are displayed in strategic places in the city. There are some steps teachers need to consider if they want to use advertisements as reading materials. First, they should introduce that the meaning of an advertisement is not something there, statically inside an advertisement, waiting to be “revealed” by a “correct” interpretation. Second, they should train the learners to get the implicit as well as an explicit meaning of the verbal texts in the advertisements. Concerning implicit (intended) meaning, train them to use the three features of contect situation. Thus using advertisement as reading materials would improve their learners’ language knowledge as well as reading skill the explicit and implicit meaning of a reading text.